Enhanced light extraction of GaN-based vertical LEDs with patterned trenches and nanostructures. (January 2017) - Lin, Tseng-Hsing; Wang, Shui-Jinn; Hung, Chien-Hsiung
Abstract: An efficient surface texturing technique that uses patterned trench etching and the selective formation of GaN nanostructures on the trench bottoms to improve the light extraction of vertical GaN-based light-emitting diodes (VLEDs) is proposed and demonstrated. Theoretical and experimental results that show the effectiveness of the proposed surface roughening scheme in improving light output power (LOP) and wall-plug efficiency (WPE) are presented and discussed. Compared with conventional VLEDs, significant improvements in LOP and WPE at 350 mA of about 37.6% and 5.1%, respectively, are obtained for the proposed VLEDs. The effective lateral light emission harvested by patterned trenches and the strongly enhanced angular randomization of photons that minimizes the total internal reflection at the GaN/air interface are responsible for the LOP and WPE improvements.